Strategi Pengembangan Usahatani Cabai Rawit Di Desa Tambelang Kecamatan Maesaan Kabupaten Minahasa Selatan - Stenly Stevanus Mandagi; Tommy Ferdy Lolowang; Jenny Baroleh (Sam Ratulangi University, 2022)
This study aims to determine and analyze the Development Strategy of cayenne pepper farming in Tambelang Village, Maesaan District, South Minahasa Regency. The research was carried out for 2 months, from January to February 2022. The research site was in Tambelang Village, Maesaan District, South Minahasa Regency. The study used primary data obtained from direct observation and interviews with respondents based on a list of questions. Secondary data were obtained from agencies related to this research. The sampling method used purposive sampling method, as many as 15 samples from the total population. The sample taken is cayenne pepper farmers who produce in 2020. The data analysis is descriptive and uses Strengths, Weakness, Opportunities and Threats (SWOT) analysis. The results showed that the results of the analysis on the SWOT matrix obtained coordinates from 1.05 to 0.48 which indicates this coordinate is in quadrant 1, which supports growth strategy. All indicators of strength in the development of cayenne pepper in Tambelang Village have the power to be developed. So that an alternative SO strategy was found, namely establishing good relations between farmers and agricultural institutions, in order to support the success of agricultural and farming development. With the development of increasingly modern technology, as well as the use of facilities and infrastructure that allow to obtain optimal results.